Muslim Intellectuals in Southeast Asia - Howard M. Federspiel (Studia Islamika, 1999)
Intellectual groups have always been important in Islamic societies and Muslim communities in Southeast Asia have been no exception. This study posits that there are four primary Muslim intellectual groups functioning in the six Muslim communities of the region. It will concentrate on a description of these four groups, discuss their spheres of activity, and anlyze their reaction to several impotrtant political and cultural factors extant in the Southeast Asian region.DOI: 10.15408/sdi.v6i1.746